Rape myth acceptance: investigating the dimensionality of the Illinois rape myth acceptance scale and the male rape myth scale. - Geldenhuis, Demi Louise (Stellenbosch : Stellenbosch University, 2023)
Thesis (MA)--Stellenbosch University, 2023.